Cooperative driving at isolated intersections based on the optimal minimization of the maximum exit time - Wu, Jia; Abbas-Turki, Abdeljalil; Perronnet, Florent (Zielona Góra: Uniwersytet Zielonogórski)
Traditional traffic control systems based on traffic light have achieved a great success in reducing the average delay of vehicles or in improving the traffic capacity. The main idea of these systems is based on the optimization of the cycle time, the phase sequence, and the phase duration. The right-of-ways are assigned to vehicles of one or several movements for a specific time. With the emergence of cooperative driving, an innovative traffic control concept, Autonomous Intersection Management (AIM), has emerged.
Keywords: cooperative driving; wireless communication; autonomous intersection management; dynamic programming